Prescription Pattern of Drugs in Hemodialysis Patients at a Tertiary Care Hospital - Anjan Palikhey,; Sonal Paudel,; Krishna Kumar Agrawaal,; Laxmi Shrestha,; Jharana Shrestha, (Journal of Universal College of Medical Sciences, 2025)
INTRODUCTION Chronic kidney disease is a worldwide issue with increasing incidence and prevalence. Patients with chronic kidney disease undergoing hemodialysis have associated co-morbidities that necessitate treatment. Consequently, the rational prescription of medications for these patients is a challenging endeavour. Investigations into the prescription patterns of medications can elucidate the drug utilization trends among hemodialysis patients and facilitate the rational use of drugs. This study aimed to evaluate the prescription pattern of drugs in hemodialysis patients at a tertiary care hospital. MATERIAL AND METHODS A hospital-based cross-sectional study was conducted at the hemodialysis unit of Universal College of Medical Sciences to assess the drug prescription patterns in patients undergoing hemodialysis. The purposive sampling technique was employed. The study involved a total of 100 patients. The data was gathered and analysed utilising SPSS version 20, with the results presented as number and percentages. RESULTS Among 100 patients, 62% were male and 38% were female. Anti-hypertensive drugs (97%) were the most prescribed drugs, followed by phosphate binders (75%), hematopoietic agents (63%), alkalinizing agents (48%). Calcium based phosphate binders were most commonly prescribed (70%) compared to non-calcium based (23%). The mean number of drugs prescribed was found to be 6.84 and the percentage of drugs prescribed from Nepal’s national essential drug list was 34.35%. CONCLUSION This study concludes that polypharmacy is prevalent among hemodialysis patients due to associated co-morbidities with chronic kidney disease. The analysis of prescribing trends is crucial for evaluating drug utilization patterns and should be conducted with greater regularity. Likewise, prescriptions should be encouraged in accordance with the national essential medicines list.